2015
DOI: 10.1007/s10803-015-2391-z
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Coordinated Communication in Infants at Heightened Risk for Autism Spectrum Disorder

Abstract: This study evaluated the extent to which developmental change in coordination of social communication in early infancy differentiates children eventually diagnosed with ASD from those not likely to develop the disorder. A prospective longitudinal design was used to compare 9 infants at heightened risk for ASD (HR) later diagnosed with ASD, to 13 HR infants with language delay, 28 HR infants with no diagnosis, and 30 low risk infants. Hierarchical Linear Modeling (HLM) analyses revealed that ASD infants exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
61
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 69 publications
8
61
0
1
Order By: Relevance
“…This result is consistent with prior work reporting that toddlers with ASD combine communicative behaviours less often than peers (Parladé & Iverson, 2015; Shumway & Wetherby, 2009; Wetherby et al, 2004) and with evidence indicating that difficulties with coordination of communicative behaviours is characteristic of communication in ASD (Shumway & Wetherby, 2009; Stone, Ousley, Yoder, Hogan, & Hepburn, 1997). …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This result is consistent with prior work reporting that toddlers with ASD combine communicative behaviours less often than peers (Parladé & Iverson, 2015; Shumway & Wetherby, 2009; Wetherby et al, 2004) and with evidence indicating that difficulties with coordination of communicative behaviours is characteristic of communication in ASD (Shumway & Wetherby, 2009; Stone, Ousley, Yoder, Hogan, & Hepburn, 1997). …”
Section: Discussionsupporting
confidence: 92%
“…HR infants were classified as language delayed (HR-LD) if they did not receive a diagnosis of ASD and either of the following criteria were met (Iverson et al, 2018; Parladé & Iverson, 2015; West, Leezenbaum, Northrup, & Iverson, in press): a) standardized scores on the MacArthur-Bates Communicative Development Inventory, Words and Sentences (CDI-II; Fenson et al, 1993) or CDI-III at or below the 10th percentile at more than one time point between 18 and 36 months (e.g.,, Ellis Weismer & Evans, 2002; Heilmann, Ellis Weismer, Evans, & Hollar, 2005); or b) standardized score on the CDI-III at or below the 10th percentile and a standardized score on the Receptive and/or Expressive Language subscales of Mullen Scale of Early Learning (MSEL; Mullen, 1995) equal to or greater than 1.5 standard deviations below the mean at 36 months (e.g.,, Landa & Garrett-Mayer, 2006; Ozonoff et al, 2010). Based on these criteria, 15 infants (9 males) were classified as HR-LD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alongside this, autism developmental science has identified variations from such normative patterns in young children at risk of or diagnosed with the condition. Thus increased parent directiveness (but not reduced responsiveness) is found in the latter part of the first year in infant siblings at risk of autism (Harker, Ibanez, Nguyen, Messinger, & Stone, ; Wan et al., ) along with reduced child attentiveness to parent, affective signalling and coordinated dyadic communication (Parlade & Iverson, ; Wan et al., ). Similar patterns are seen in established autism as well as in other developmental disabilities (Blacher, Baker, & Kaladjian, ; Doussard‐Roosevelt, Joe, Bazhenova, & Porges, ).…”
Section: Targets and Mechanisms In Psychosocial Autism Interventionmentioning
confidence: 99%
“…With regard to gesture, Parladé and Iverson (2015) examined longitudinal trajectories of production of gesture-vocalization coordinations (i.e., instances in which the two behaviors were produced with temporal overlap between them) sampled during naturalistic play sessions at home at 8, 10, 12, 14, and 18 months. They reported that while gesture-vocalization coordinations were initially delayed in both HR-LD and HR-ASD infants, by 12 months of age these coordinations had begun to emerge in HR-LD infants and grew at a rate comparable to those of HR infants with neither an ASD nor an LD diagnosis (HR-No Diagnosis; HR-ND) and of a group of infants with a typically-developing older sibling and no family history of ASD (Low Risk infants; LR).…”
mentioning
confidence: 99%